CGRP – a target for acute therapy in migraine: Clinical data. (March 2019) - Messina, Roberta; Goadsby, Peter J
Background: A better understanding of the mechanisms underlying the migraine attack has reinforced the concept that migraine is a complex brain disease, and has paved the way for the development of new migraine specific acute treatments. In recent years, targeting the calcitonin gene-related peptide and its receptors has been one of the most promising pharmacological strategies for both acute and preventive treatment of migraine. Findings: Randomized double-blind placebo-controlled trials have demonstrated the superiority of small molecule calcitonin gene-related peptide receptor antagonists (gepants) over placebo in treating acute migraine attacks measured as the two-hour pain free endpoint. Gepants also improved migraine associated symptoms, such as nausea, photophobia and phonophobia. Two of the class have had their development stopped because of hepatotoxicity, which is emerging as being due to metabolites. Gepants have a good tolerability and can be safely used in patients with stable cardiovascular disease. Conclusion: Exciting results have been obtained targeting the calcitonin gene-related peptide pathway to abort acute migraine attacks, thus reinforcing the relevance of mechanism-based treatments specific for migraine.